A service yips experiences in badminton players - Jeon, J.-Y.; Kim, H.-J.; Kim, J.-S.; Park, S.-H. (Korean Journal of Sport Science, 2021)
Purpose: This study aims to investigate the experience of service yips in badminton players in depth through using grounded theory method. Methods: We collected data from in-depth interviews with 14 participants in total, consisting of badminton players who experienced service yips, their doubles partners and coaches. The collected raw data were analyzed base on derive transcription, coding and paradigm models through grounded theory method. Results: First, as a result, 59 concepts, 31 subcategories and 15 categories in regard to badminton service yips were deduced from open coding. Second, in axial coding, it was structured in a paradigm model by categories such as service yips, service mistakes, service proficiency, service anxiety, the imprinting experiences, the importance competition, the pressure of achievement, service practice, psychological control, tactical handling, support from partners, leaders` coaching, advice from experienced ones, overcoming yips and persistent yips. Third, selective coding resulted in `Badminton service yips` as the core category of this study. `Badminton service yips` is a chronic performance impairment associated with badminton players making severe errors in swing motion on a service not intended by them that it is due to physiological or psychological symptoms such as hand tremors, overall body stiffness, arms stiffness, overstress, overanxiety, and concern over service mistakes. Conclusions: We expect our study can be a theoretical foundation for understanding and explanation of `Badminton service yips` and a useful reference for badminton players suffering from psychological difficulties caused by their service yips. The findings in this study should be considered for the development of potential strategies for overcoming the badminton service yips.